Природа і зміст політичної служби в Україні - Малиновський, Валентин Ярославович; Malynovskyi, Valentyn Ya. (Національний університет «Юридична академія України імені Ярослава Мудрого», 2018)
У статті здійснено аналіз політичної служби як одного з видів публічної служби. Розкрито особливості політичних посад в державних органах, зокрема політичний характер цих посад, що суттєво відрізняє їх від інших посад публічної служби, зокрема, державної служби. Також визначено поняття «політичний діяч (політик)», специфічні принципи, якими керуються у своїй діяльності політичні діячі. Наголошено на відсутності законодавчого врегулювання цілої низки керівних посад у державних органах, на які дія нового Закону України «Про державну службу» не поширюється.

Problem setting. A thorough scientific understanding of political activity in state bodies, and, accordingly, political service, is an actual scientific topic. It acquired particular significance in the context of the reform of public administration identified by the Strategy for 2016–2020. Recent research and publications analysis. Considerable attention of scientists from all over the world is paid to the study of the civil, political, public service, this topic is at the center of attention by V. Averyanov, L. Beloy-Tionova, K.-H. Cho, R. A. Cropf, S. Kim, S. Kivalov, N. Kolisnichenko, O. Krupchan, J. G. McGann, T. Motrenko, K. Namkoong, Ch. B. Newswander, N. Runowa, J. L. Wagner, T. Zeliuk et al. But one needs to study in more detail the political service in Ukraine. Paper objective. The purpose of the article is to describe the political service as one of the types of public service. Paper main body. The political component of the public service is a relatively new domestic institution, although the debate on the delineation of policy and administration in the field of public administration has been under way since W. Wilson, who in 1887 clearly divided his policy and administration into his essay «The Study of Administration». Ukraine has gone through a difficult path to implement a mechanism for distinguishing between politics and administration in the public sphere.For the first time, the idea of demarcation of political and administrative positions with the need to introduce a political figure (politician) in the official sphere appeared in the Concept of Administrative Reform in Ukraine since 1998. However, only in 2001, political positions were officially recognized in accordance with the Decree of the President of Ukraine «On next steps for further implementation of administrative reform in Ukraine». Political positions are one of the types of public service posts, which, by their peculiarities and politico-legal principles, differ significantly from other public service positions, in particular civil service. The political nature of these positions is determined by: a special procedure for appointment to a post regulated by the constitution and laws; a special procedure for dismissal and termination of authority; special types of responsibility, which has signs of public, mainly political, for the consequences of being a political figure. In their activities, political figures are guided by specific principles: the presence of a clear political position; activity and initiative; political morality (observance of its political position). Conclusions of the research. The political service in Ukraine generally received a legislative settlement. The article also emphasizes the lack of legislative regulation of a number of executive positions in state bodies, which are not subject to the new Law of Ukraine «On Civil Service».
Nature and content of political service in Ukraine
Keywords: політична служба; публічна служба; державна служба; політична посада; політичний діяч (політик); political service; public service; civil service; political position; political figure (politician)